Higher maternal BMI early in pregnancy is associated with overweight and obesity in young adult offspring in Thailand - Sakaewan Ounjaijean; Antika Wongthanee; Kanokwan Kulprachakarn; Amaraporn Rerkasem; Sakda Pruenglampoo; Ampica Mangklabruks; Kittipan Rerkasem; José G. B. Derraik (BMC, 2021)
Abstract Background Rates of overweight and obesity among women of reproductive age have been steadily increasing worldwide and in Thailand. There is mounting evidence that maternal obesity during pregnancy is associated with an increased risk of obesity and other adverse health outcomes in the offspring, but such data are lacking for Thailand. We examined the associations between maternal body mass index (BMI) and anthropometry (particularly the likelihood of obesity) and cardiometabolic parameters in young adult offspring. Methods This was a prospective follow-up study of a birth cohort in Chiang Mai (Thailand). Pregnant women carrying singletons were recruited at their first antenatal visit (< 24 weeks of gestation) and followed until delivery in 1989-1990. Participants were their young adult offspring followed up in 2010. Maternal BMI was recorded at the first antenatal visit. The offspring underwent clinical assessments, including anthropometry, lipid profile, insulin sensitivity (HOMA-IR), blood pressure, and carotid intima-media thickness. The primary outcome of interest was the likelihood of obesity in the offspring. Results We assessed 628 young adults (54% were females) at 20.6 ± 0.5 years of age (range 19.1-22.1 years). The young adult offspring of mothers with overweight/obesity was 14.1 kg (95%CI 9.7, 18.5; p < 0.0001) and 9.4 kg (95% CI 6.1, 12.8; p < 0.0001) heavier than those born to mothers with underweight or normal weight, respectively, and had BMI 3.46 kg/m2 (95%CI 2.26, 4.67; p < 0.0001) and 5.27 kg/m2 (95%CI 3.67, 8.68; p < 0.0001) greater, respectively. For every 1-kg/m2 increase in maternal BMI, the adjusted odds ratio (aOR) of offspring obesity was 25% greater (95%CI 1.10, 1.42; p < 0.001). Thus, the aOR of obesity in offspring of mothers with overweight/obesity was 4.6 times greater (95%CI 1.86, 11.26; p < 0.001) and nearly 17-fold greater (95%CI 1.96, 146.4; p = 0.010) compared to young adults born to mothers with normal weight or underweight, respectively. There were no observed associations between maternal BMI status and offspring metabolism or blood pressure. Discussion Maternal overweight/obesity early in pregnancy was associated with increased BMI and greater odds of obesity in their young adult offspring in Thailand. These findings highlight the public health importance of fostering healthier lifestyle choices among women of reproductive age.